Crossing the border : constructions of borderline personality disorder within the South African context: a discourse analytic study - Elphick, Marie-Clair (Rhodes University, Faculty of Humanities, Department of Psychology)
This research aims to open up for critical discussion the effects of the discourses employed by mental health professionals in relation to the diagnosis of BPO, with a view of questioning the discursive practices available within a South African context. This discussion will situate identified discourses in relation to the subjects and objects to which it refers in an attempt to identify and interrogate dominant discourses which circulate to oppress and discriminate against female 'others' within the mental health setting. This discussion will serve to challenge mainstream, traditional psychology by questioning the utility of deploying these concepts within a South African context as well as the effects this deployment may have. A discourse analytic methodology is employed to identify the constructions of BPO by five mental health professionals working within a government setting. The analysis aims at interrogating the broader role of the identified discourses in supporting institutions, preserving power relations and transmitting ideological practices. Ultimately the aim of the research is to open up for critical debate, through the example of psychology and psychiatry's treatment of BPO; constituted as 'other', the possibility that there may be deleterious consequences for the wholesale acceptance of traditional psychological understandings by mental health professionals working within a South African context.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Borderline personality disorder -- South Africa; Borderline personality disorder -- Diagnosis